Stomach cancer epidemic in Chinese mainland: Current trends and future predictions - Wenxuan Zhu; Wanyue Dong; Yunning Liu; Ruhai Bai; Jinjiao Li (Chinese Medical Journal)
Abstract. Background:. China is one of the countries with the highest burdens of stomach cancer. The objective of this study was to analyze long-term trends in the incidence and mortality of stomach cancer in Chinese mainland from 1990 to 2019 and to make projections until 2030. Methods:. Data on stomach cancer were extracted from the Global Burden of Diseases Study 2019. Population data were extracted from the Global Burden of Diseases Study 2019 and World Population Prospects 2019. An age–period–cohort framework and decomposition analysis were used in this study. Results:. The net drift for the incidence of stomach cancer was 0.2% (95% confidence interval [CI]: 0, 0.4%) per year for men and –1.8% (95% CI: –2.0%, –1.6%) for women. The net drift for mortality was –1.6% (95% CI: –1.8%, –1.3%) per year for men and –3.3% (95% CI: –3.5%, –3.1%) for women. In the last 10–15 years, the risk of stomach cancer occurrence and death has continued to decline for both sexes. Regarding birth cohorts, although the risk of stomach cancer death decreased in general among women and men born after 1920, the risk of occurrence increased in recent birth cohorts (men born after 1970 and women born after 1985). It is expected that the age-standardized incidence will increase among men and decrease among women, and age-standardized mortality will decrease for both sexes. The largest contributor to the projected increase in incident cases and deaths is population aging, and elderly individuals are projected to have an increased proportion of occurrence and death. Conclusions:. In the past three decades, the incidence of stomach cancer among men has increased in Chinese mainland, and this trend is projected to continue. Aging will be the main contributor to future increased stomach cancer occurrence and deaths. To reduce the health impact of stomach cancer, more efforts are needed.